Texture and terahertz analysis of YBa2Cu3O7 grown onto LaAlO3 by the chemical solution deposition technique. Issue 1 (2nd January 2021) - Sanchez Cornejo, H.; De Los Santos Valladares, L.; Kamboj, V. S.; Bustamante Dominguez, A.; González, J. C.; Osorio Anaya, A. M.; Moreno, N. O.; Beere, H. E.; Ritchie, D. A.; Newton, P. J.; Barnes, C. H. W.
ABSTRACT: We analyze in-plane and out-of-plane texture and terahertz analysis of a YBa2 Cu3 O7-δ (YBCO) film deposited by chemical solution deposition technique onto LaAlO3 (100) substrate. X-ray diffraction reveals the presence of (00 l ) reflections for the YBCO phase. The out-of-plane texture, measured by a rocking curve, shows two sub-layers with Δω = 0.45° and 1.8°. The value of the c -axis fraction of the crystallites is 81%. Also, the in-plane texture was studied by ϕ-scan measurements of the (102) reflection, displaying mostly a colony of c -axis oriented grains, and two colonies of a -axis oriented grains onto the YBCO surface. In addition, the temperature dependence of the magnetization measurement revealed a critical temperature of 90 K, typical for YBCO superconductor material. From the temperature-dependent optical conductivity of YBCO, we observe an absorption feature at ≈1.57 THz, which redshifts with increasing temperature.